Stent loaded with radioactive Iodine-125 seeds for adenoid cystic carcinoma of central airway: A case report of innovative brachytherapy - Ke, Mingyao; Zeng, Junli; Chen, Zhide; Huang, Rui; Wu, Xuemei; Chu, Shuyuan (Frontiers in Oncology, 2023)
Adenoid cystic carcinoma (ACC) of central airway is very rare. More than half of ACCs are unresectable for tumor extension. There’s rare report on local ACCs only in central airway. We present a case of ACC in central airway who underwent an innovative brachytherapy. A 44-year-old woman was diagnosed with primary ACC in central airway without regional lymphadenopathy or metastatic disease. Stenosis was observed in lower trachea and both left and right main bronchi (stenosis in lumen ≥50%) with bronchoscopy. The tumor was unresectable due to local extension. A Y-shaped and stainless-steel stent loaded with radioactive 125I seeds was placed in the central airway using bronchoscope. The number and distribution of 125I seeds were planed using treatment planning system. The stent was removed three months later. The patient tolerated the procedure well. She was alive without relapse three years after removing the stent with 125I seeds. This case demonstrates the successful use of stent with radioactive 125I seeds for unresectable ACCs in central airway. In the procedure, the stent was placed with bronchoscope and under the vision from bronchoscope. This innovative brachytherapy is well-tolerated, safe, precise and individualized designed. The patient with unresectable ACCs could get a long-term relapse-free survival. Clinical trials could be taken to validate its effectiveness and tolerability in patients with ACCs of central airway.